P2 type sodium ion battery positive electrode material and preparation method thereof

By introducing Gd/Ba double-doped and composite fast ion conductor cladding into the positive electrode material of P2 type sodium ion battery, the problem of insufficient rate performance and cycle stability at high voltage is solved, and excellent high voltage performance is achieved , suitable for high power applications.

CN119480949AActive Publication Date: 2025-02-18HUNAN MEITE XINCAILIAO SCI & TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411420566.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-18
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing P2 sodium ion battery positive electrode materials have insufficient rate performance and cycle stability at high voltages, making it difficult to meet the needs of high power applications.

Method used

The Gd/Ba double-doped NaaNixMn2xGdyBazO2 material is used as the matrix core of the core-shell structure, and the mixed conductor layer of Ti(HPO4)2 and MgHPO4 is coated on its surface to form a composite fast ion conductor coating structure.

Benefits of technology

The rate performance and cycle performance of the material are significantly improved at high voltages, and are suitable for high-power fields such as start-stop power supplies and power tools.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480949A_ABST
    Figure CN119480949A_ABST
Patent Text Reader

Abstract

The invention provides a P2 type sodium ion battery positive electrode material and a preparation method thereof, the P2 type sodium ion battery positive electrode material is of a core-shell structure and comprises a NaaNixMn2xGdyBazO2 material as a matrix core and a conductor coating layer coating the surface of the matrix core material, the conductor coating layer material is a mixture of Ti (HPO4) 2 and MgHPO4, 0.6 < = a < = 0.7, 0.005 < = y < = 0.02, 0.001 < = z < = 0.01, and 3x + y + z = 1. The P2 type sodium ion battery positive electrode material has excellent rate capability and cycle performance under high voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and in particular to a P2 type sodium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] Sodium-ion batteries based on P2-type positive electrode materials have become the most promising alternatives to lithium-ion batteries or lead-acid batteries in high-power fields such as start-stop power supplies due to their environmental friendliness, overdischarge, excellent high and low temperature performance, and rate performance. Although P2-type sodium-ion battery positive electrode materials have excellent cycle performance under conventional voltages, their capacity is relatively low; when the upper voltage is increased to above 4.2V, this type of material has considerable capacity and median voltage, but the irreversible phase transition from P2 phase to O2 phase leads to poor cycle stability. Although the rate performance of P2-type materials is better than that of O3-type materials, the rate performance under high voltage needs to be further improved. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a P2 type sodium ion battery positive electrode material and a preparation method, a Gd / Ba dual-doped, composite fast ion conductor-coated sodium ion battery positive electrode material, which has excellent rate performance and cycle performance under high voltage and is expected to be applied in high-power fields such as start-stop power supplies and power tools.

[0004] To achieve the above object, the technical solution adopted by the present invention is: a P2 type sodium ion battery positive electrode material, the P2 type sodium ion battery positive electrode material is a core-shell structure, including Na as the core of the matrix a Ni x Mn 2x G y Ba z O2 material and a conductor coating layer coated on the surface of the matrix core material, the conductor coating layer material is a mixture of Ti(HPO4)2 and MgHPO4, wherein 0.6≤a≤0.7, 0.005≤y≤0.02, 0.001≤z≤0.01, and satisfies 3x+y+z=1.

[0005] The above-mentioned P2 type sodium ion battery cathode material is a core-shell structure, and the core material is doped with Gd / Ba at the same time. a Ni x Mn 2x G y Ba z O2 material is used as the matrix core, and the conductor coating layer on the surface of the matrix core material is a mixture of Ti(HPO4)2 and MgHPO4. Through the mixture of coating layer materials Ti(HPO4)2 and MgHPO4, it has excellent rate performance and cycle performance under high voltage.

[0006] Preferably, 0.65≤a≤0.68.

[0007] Preferably, in the P2 type sodium ion battery positive electrode material, the coating layer material accounts for 0.1% to 1% of the mass of the P2 type sodium ion battery positive electrode material.

[0008] The above-mentioned P2 type sodium ion battery positive electrode material has better rate performance and cycle performance at high voltage.

[0009] Preferably, 1≤y / z≤2, 0.008≤y≤0.15.

[0010] The above-mentioned P2 type sodium ion battery positive electrode material has better rate performance and cycle performance at high voltage.

[0011] Preferably, in the conductor coating layer material, the weight ratio of Ti(HPO4)2 to MgHPO4 is (2-8):1.

[0012] The above-mentioned P2 type sodium ion battery positive electrode material, when the weight ratio of Ti(HPO4)2 and MgHPO4 in the conductor coating layer material is (2 to 8):1, has better rate performance and cycle performance at high voltage.

[0013] Preferably, in the conductor coating layer material, the weight ratio of Ti(HPO4)2 and MgHPO4 is (3-5):1.

[0014] In the above-mentioned P2 type sodium ion battery positive electrode material, when the weight ratio of Ti(HPO4)2 and MgHPO4 in the conductor coating layer material is (3 to 5):1, it has better rate performance and cycle performance at high voltage.

[0015] The present invention also provides a method for preparing any of the above-mentioned P2 type sodium ion battery positive electrode materials, the method comprising the following steps:

[0016] (1) The sodium source, nickel source, manganese source, gadolinium source and barium source are mixed evenly according to the stoichiometric ratio and then subjected to the first heat treatment to obtain the P2 matrix Na a Ni x Mn 2x G y Ba z O2; the first heat treatment holding temperature is 850 ℃ ~ 1050 ℃, the holding time is 8 to 16 hours, the heating rate is 3 to 5 ℃ / min, and the sintering atmosphere is air;

[0017] (2) The Na obtained in step (1) a Ni x Mn 2x Gy Ba z O2 material is crushed to a particle size of D00 ≥ 0.5 μm, 4.0 μm ≤ D50 ≤ 5.5 μm, and D100 ≤ 14 μm;

[0018] (3) the material obtained in step (2) is uniformly mixed with Ti(HPO4)2 and MgHPO4 according to a mass ratio, and then subjected to a second heat treatment to obtain a high-voltage and high-rate P2 type sodium ion battery positive electrode material; the second heat treatment has a holding temperature of 650° C. to 850° C., a holding time of 4 to 10 hours, a heating rate of 3 to 5° C. / min, and an air sintering atmosphere;

[0019] (4) The material obtained in step (3) is crushed to a particle size satisfying D00 ≥ 0.6 μm, 4.5 μm ≤ D50 ≤ 6.5 μm, and D100 ≤ 16 μm.

[0020] Preferably, the sodium source is one or more of sodium carbonate, sodium hydroxide and sodium oxalate.

[0021] Preferably, the nickel source is one or more of its oxide, oxalate or hydroxide.

[0022] Preferably, the manganese source and gadolinium source are their corresponding oxides.

[0023] Preferably, the barium source is one or both of its carbonate and oxalate.

[0024] The present invention also provides a sodium ion secondary battery, which comprises any one of the above-mentioned P2 type sodium ion battery positive electrode materials.

[0025] The beneficial effects of the present invention are as follows: the present invention provides a P2 type sodium ion battery positive electrode material and a preparation method thereof, wherein the P2 type sodium ion battery positive electrode material of the present invention is a core-shell structure, wherein the core material is doped with Gd / Ba at the same time, and Na a Ni x Mn 2x G y Ba z O2 material is used as the matrix core, and the conductor coating layer on the surface of the matrix core material is a mixture of Ti(HPO4)2 and MgHPO4. Through the combination of Ti(HPO4)2 and MgHPO4, the coating layer has excellent rate performance and cycle performance under high voltage. It is expected to be applied in high-power fields such as start-stop power supplies and power tools.

[0026] The P2 type sodium ion battery positive electrode material of the present invention has the following advantages:

[0027] 1) Ba has a weaker electronegativity and a larger ionic radius, which can effectively weaken O2- To Na + The attraction of Na + diffusion barrier, constructing the internal Na + Fast track.

[0028] 2) The high lattice energy between Gd and O (Gd—O, 716 kJ / mol) can effectively improve the stability of the crystal structure and inhibit the escape of oxygen under high voltage, thereby improving the cycle stability of the material.

[0029] 3) Surface-coated composite fast ion conductors can construct Na + Fast channel, thereby improving the material's rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a rate discharge curve diagram of the positive electrode material of a P2 type sodium ion battery according to an embodiment of the present invention.

[0031] Figure 2 This is a rate discharge curve diagram of the positive electrode material of a P2 type sodium ion battery according to an embodiment of the present invention. DETAILED DESCRIPTION

[0032] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0033] Example 1

[0034] As a P2 type sodium ion battery positive electrode material of an embodiment of the present invention, the P2 type sodium ion battery positive electrode material is a core-shell structure, including Na as the core of the matrix 0.67 Ni x Mn 2x G y Ba z O2 material and a conductor coating layer coated on the surface of the matrix core material, the conductor coating layer material is a mixture of Ti(HPO4)2 and MgHPO4, wherein 0.005≤y≤0.02, 0.001≤z≤0.01, and satisfies 3x+y+z=1.

[0035] The preparation method of the positive electrode material of the P2 type sodium ion battery in this embodiment comprises the following steps:

[0036] S1. Weigh sodium carbonate, nickel oxide, manganese dioxide, gadolinium oxide and barium carbonate in proportion to prepare Na 0.67 Ni 0.33 Mn 0.66 G 0.005 Ba 0.005 O2, after all the raw materials are mixed evenly, they are kept at 970℃ for 14h, with a heating rate of 4℃ / min, and the sintering atmosphere is air.

[0037] S2. The material obtained in S1 is crushed by jaw crusher, roller mill and air flow mill in turn. The D00, D50 and D100 of the obtained material are 0.53 μm, 4.84 μm and 12.42 μm respectively.

[0038] S3, weigh the materials obtained in S2, Ti(HPO4)2(TP), and MgHPO4(MP) in proportion to prepare Na 0.67 Ni 0.33 Mn 0.66 G 0.005 Ba 0.005 O2@0.4%TP&0.1%MP, the % in the formula indicates that when the raw materials are added, Ti(HPO4)2 and MgHPO4 account for the proportion of Na 0.67 Ni 0.33 Mn 0.66 G 0.005 Ba 0.005 The theoretical content of O2@0.4%TP&0.1%MP, all raw materials are mixed evenly and kept at 750℃ for 8h. The heating rate is 3℃ / min, and the sintering atmosphere is air;

[0039] S4. The material obtained in S3 is crushed by jaw crusher, roller crusher and air flow mill in sequence. The D00, D50 and D100 of the obtained material are 0.65 μm, 5.68 μm and 15.34 μm respectively.

[0040] Example 2

[0041] As a P2 type sodium ion battery positive electrode material in an embodiment of the present invention.

[0042] The preparation method of the positive electrode material of the P2 type sodium ion battery in this embodiment comprises the following steps:

[0043] S1. Weigh sodium carbonate, nickel oxide, manganese dioxide, gadolinium oxide and barium carbonate in proportion to prepare Na 0.67 Ni 0.328 Mn 0.656 G 0.01 Ba 0.006 O2, and the raw materials are mixed evenly and kept at 970℃ for 14h. The heating rate is 4℃ / min, and the sintering atmosphere is air.

[0044] S2. The material obtained in S1 is crushed by jaw crusher, roller mill and air flow mill in sequence. The D00, D50 and D100 of the obtained material are 0.55 μm, 4.88 μm and 12.52 μm respectively.

[0045] S3, weigh the materials obtained in S2, Ti(HPO4)2(TP), and MgHPO4(MP) in proportion to prepare Na 0.67 Ni0.328 Mn 0.656 G 0.01 Ba 0.006 O2@0.4%TP&0.1%MP, all raw materials are mixed evenly and kept at 750℃ for 8h. The heating rate is 3℃ / min, and the sintering atmosphere is air.

[0046] S4. The material obtained in S3 is crushed by jaw crusher, roller mill and air flow mill in sequence. The D00, D50 and D100 of the obtained material are 0.68 μm, 5.71 μm and 15.44 μm respectively.

[0047] Example 3

[0048] As a P2 type sodium ion battery positive electrode material in an embodiment of the present invention.

[0049] The preparation method of the positive electrode material of the P2 type sodium ion battery in this embodiment comprises the following steps:

[0050] S1. Weigh sodium carbonate, nickel oxide, manganese dioxide, gadolinium oxide and barium carbonate in proportion to prepare Na 0.67 Ni 0.321 Mn 0.642 G 0.03 Ba 0.007 O2, and the raw materials are mixed evenly and kept at 970℃ for 14h. The heating rate is 4℃ / min, and the sintering atmosphere is air.

[0051] S2. The material obtained in S1 is crushed by jaw crusher, roller mill and air flow mill in turn. The D00, D50 and D100 of the obtained material are 0.57 μm, 4.91 μm and 12.68 μm.

[0052] S3, weigh the materials obtained in S2, Ti(HPO4)2(TP), and MgHPO4(MP) in proportion to prepare Na 0.67 Ni 0.321 Mn 0.642 G 0.03 Ba 0.007 O2@0.4%TP&0.1%MP, all raw materials are mixed evenly and kept at 750℃ for 8h. The heating rate is 3℃ / min, and the sintering atmosphere is air.

[0053] S4. The material obtained in S3 is crushed by jaw crusher, roller mill and air flow mill in sequence. The D00, D50 and D100 of the obtained material are 0.70 μm, 5.74 μm and 15.49 μm respectively.

[0054] Example 4

[0055] As a P2 type sodium ion battery positive electrode material in an embodiment of the present invention.

[0056] The preparation method of the positive electrode material of the P2 type sodium ion battery in this embodiment comprises the following steps:

[0057] S1. Weigh sodium carbonate, nickel oxide, manganese dioxide, gadolinium oxide and barium carbonate in proportion to prepare Na 0.67 Ni 0.314 Mn 0.628 G 0.05 Ba 0.008 O2, and the raw materials are mixed evenly and kept at 970℃ for 14h. The heating rate is 4℃ / min, and the sintering atmosphere is air.

[0058] S2. The material obtained in S1 is crushed by jaw crusher, roller mill and air flow mill in sequence. The D00, D50 and D100 of the obtained material are 0.59 μm, 4.95 μm and 12.71 μm respectively.

[0059] S3, weigh the materials obtained in S2, Ti(HPO4)2(TP), and MgHPO4(MP) in proportion to prepare Na 0.67 Ni 0.314 Mn 0.628 G 0.05 Ba 0.008 O2@0.4%TP&0.1%MP, all raw materials are mixed evenly and kept at 750℃ for 8h. The heating rate is 3℃ / min, and the sintering atmosphere is air.

[0060] S4. The material obtained in S3 is crushed by jaw crusher, double roller and air flow mill in sequence. The D00, D50 and D100 of the obtained material are 0.71 μm, 5.77 μm and 15.61 μm.

[0061] Example 5

[0062] As a P2 type sodium ion battery positive electrode material in an embodiment of the present invention.

[0063] The preparation method of the positive electrode material of the P2 type sodium ion battery in this embodiment comprises the following steps:

[0064] S1. Weigh sodium carbonate, nickel oxide, manganese dioxide, gadolinium oxide and barium carbonate in proportion to prepare Na 0.67 Ni 0.328 Mn 0.656 G 0.01 Ba 0.006 O2, and the raw materials are mixed evenly and kept at 970℃ for 14h. The heating rate is 4℃ / min, and the sintering atmosphere is air.

[0065] S2. The material obtained in S1 is crushed by jaw crusher, roller mill and air flow mill in sequence. The D00, D50 and D100 of the obtained material are 0.55 μm, 4.88 μm and 12.52 μm respectively.

[0066] S3, weigh the materials obtained in S2, Ti(HPO4)2(TP), and MgHPO4(MP) in proportion to prepare Na 0.67 Ni 0.328 Mn 0.656 G 0.01 Ba 0.006 O2@0.08%TP&0.02%MP, all raw materials are mixed evenly and kept at 750℃ for 8h. The heating rate is 3℃ / min, and the sintering atmosphere is air.

[0067] S4. The material obtained in S3 is crushed by jaw crusher, roller mill and air flow mill in sequence. The D00, D50 and D100 of the obtained material are 0.64 μm, 5.65 μm and 15.24 μm respectively.

[0068] Example 6

[0069] As a P2 type sodium ion battery positive electrode material in an embodiment of the present invention.

[0070] The preparation method of the positive electrode material of the P2 type sodium ion battery in this embodiment comprises the following steps:

[0071] S1. Weigh sodium carbonate, nickel oxide, manganese dioxide, gadolinium oxide and barium carbonate in proportion to prepare Na 0.67 Ni 0.328 Mn 0.656 G 0.01 Ba 0.006 O2, and the raw materials are mixed evenly and kept at 970℃ for 14h. The heating rate is 4℃ / min, and the sintering atmosphere is air.

[0072] S2. The material obtained in S1 is crushed by jaw crusher, roller mill and air flow mill in sequence. The D00, D50 and D100 of the obtained material are 0.55 μm, 4.88 μm and 12.52 μm respectively.

[0073] S3, weigh the materials obtained in S2, Ti(HPO4)2(TP), and MgHPO4(MP) in proportion to prepare Na 0.67 Ni 0.328 Mn 0.656 G 0.01 Ba 0.006 O2@0.8%TP&0.2%MP, all raw materials are mixed evenly and kept at 750℃ for 8h. The heating rate is 3℃ / min, and the sintering atmosphere is air.

[0074] S4. The material obtained in S3 is crushed by jaw crusher, roller crusher and air flow mill in sequence. The D00, D50 and D100 of the obtained material are 0.68 μm, 5.74 μm and 15.68 μm respectively.

[0075] Example 7

[0076] As a P2 type sodium ion battery positive electrode material of an embodiment of the present invention, the only difference between this embodiment and Example 2 is the content and proportion of Ti(HPO4)2(TP) and MgHPO4(MP) in the coating layer material.

[0077] Na 0.67 Ni 0.328 Mn 0.656 G 0.01 Ba 0.006 O2@0.4%TP&0.2%MP.

[0078] Example 8

[0079] As a P2 type sodium ion battery positive electrode material of an embodiment of the present invention, the only difference between this embodiment and Example 2 is the content and proportion of Ti(HPO4)2(TP) and MgHPO4(MP) in the coating layer material.

[0080] Na 0.67 Ni 0.328 Mn 0.656 G 0.01 Ba 0.006 O2@0.45%TP&0.15%MP.

[0081] Example 9

[0082] As a P2 type sodium ion battery positive electrode material of an embodiment of the present invention, the only difference between this embodiment and Example 2 is the content and proportion of Ti(HPO4)2(TP) and MgHPO4(MP) in the coating layer material.

[0083] Na 0.67 Ni 0.328 Mn 0.656 G 0.01 Ba 0.006 O2@0.5%TP&0.1%MP.

[0084] Example 10

[0085] As a P2 type sodium ion battery positive electrode material of an embodiment of the present invention, the only difference between this embodiment and Example 2 is the content and proportion of Ti(HPO4)2(TP) and MgHPO4(MP) in the coating layer material.

[0086] Na 0.67Ni 0.328 Mn 0.656 G 0.01 Ba 0.006 O2@0.3%TP&0.3%MP.

[0087] Embodiment 11

[0088] As a P2 type sodium ion battery positive electrode material of an embodiment of the present invention, the only difference between this embodiment and Example 2 is the content and proportion of Ti(HPO4)2(TP) and MgHPO4(MP) in the coating layer material.

[0089] Na 0.67 Ni 0.328 Mn 0.656 G 0.01 Ba 0.006 O2@0.8%TP&0.1%MP.

[0090] Comparative Example 1

[0091] As a P2 type sodium ion battery positive electrode material of the comparative example of the present invention, the difference between this comparative example and Example 2 is that there is no core-shell structure and no coating layer. The chemical formula of the material is

[0092] Na 0.67 Ni 0.328 Mn 0.656 G 0.01 Ba 0.006 O2.

[0093] Comparative Example 2

[0094] As a P2 type sodium ion battery positive electrode material of the comparative example of the present invention, the difference between this comparative example and Example 2 is that the coating layer is Ti(HPO4)2, the coating layer does not contain MgHPO4, and the amount of MgHPO4 is supplemented by Ti(HPO4)2. The chemical formula of the material is Na 0.67 Ni 0.328 Mn 0.656 G 0.01 Ba 0.006 O2@0.5%TP.

[0095] Comparative Example 3

[0096] As a P2 type sodium ion battery positive electrode material of the comparative example of the present invention, the difference between this comparative example and Example 2 is that the coating layer is MgHPO4, the coating layer does not contain Ti(HPO4)2, and the amount of Ti(HPO4)2 is supplemented by MgHPO4. The chemical formula of the material is Na 0.67 Ni 0.328 Mn 0.656 G 0.01 Ba0.006 O2@0.5%MP.

[0097] Comparative Example 4

[0098] As a P2 type sodium ion battery positive electrode material of the comparative example of the present invention, the difference between this comparative example and Example 2 is that Gd is not doped, and the content of Gd is supplemented by Ba. The chemical formula of the material is Na 0.67 Ni 0.328 Mn 0.656 Ba 0.016 O2@0.4%TP&0.1%MP.

[0099] Comparative Example 5

[0100] As a P2 type sodium ion battery positive electrode material of the comparative example of the present invention, the difference between this comparative example and Example 2 is that Ba is not doped, and the Ba content is supplemented by Gd. The chemical formula of the material is Na 0.67 Ni 0.328 Mn 0.656 G 0.016 O2@0.4%TP&0.1%MP.

[0101] Experimental methods

[0102] Electrochemical performance

[0103] The electrochemical performance test uses a half-cell (2.0V-4.25V), and the key parameters are as follows:

[0104] 1) Positive electrode material: acetylene black: PVDF = 85:10:5

[0105] 2) Negative electrode: sodium sheet

[0106] 3) Electrolyte: 1.0M NaPF6 (DEC:EC:EMC=1:1:1, Vol% with 8% FEC)

[0107] The electrochemical properties of the positive electrode materials of the P2 type sodium ion battery of the embodiment and the comparative example are shown in Table 1.

[0108] Table 1 Electrochemical performance of P2 type sodium ion battery cathode materials

[0109]

[0110]

[0111] As shown in Table 1, the cathode material of the P2 type sodium ion battery of the present invention is a core-shell structure, and the core material is doped with Gd / Ba at the same time. 0.67 Ni x Mn 2x G yBa z O2 material is used as the matrix core, and the conductor coating layer on the surface of the matrix core material is a mixture of Ti(HPO4)2 and MgHPO4. Through the mixture of coating layer materials Ti(HPO4)2 and MgHPO4, it has excellent rate performance and cycle performance under high voltage, and improves the cycle performance under high temperature conditions.

[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A P2 type sodium ion battery positive electrode material, characterized in that: The P2 type sodium ion battery positive electrode material is a core-shell structure, including Na a Ni x Mn 2x G y Ba z O2 material and a conductor coating layer coated on the surface of the matrix core material, the conductor coating layer material is a mixture of Ti(HPO4)2 and MgHPO4, wherein 0.6≤a≤0.7, 0.005≤y≤0.02, 0.001≤z≤0.01, and satisfies 3x+y+z=1.

2. The P2 type sodium ion battery positive electrode material according to claim 1, characterized in that: 0.65≤a≤0.68。 3. The P2 type sodium ion battery positive electrode material according to claim 1, characterized in that: In the P2 type sodium ion battery positive electrode material, the coating layer material accounts for 0.1% to 1% of the mass of the P2 type sodium ion battery positive electrode material.

4. The P2 type sodium ion battery positive electrode material according to claim 1, characterized in that: 1≤y / z≤2, 0.008≤y≤0.

15.

5. The P2 type sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: In the conductor coating material, the weight ratio of Ti(HPO4)2 to MgHPO4 is (2-8):

1.

6. The P2 type sodium ion battery positive electrode material according to claim 5, characterized in that: In the conductor coating layer material, the weight ratio of Ti(HPO4)2 and MgHPO4 is (3-5):

1.

7. The method for preparing a positive electrode material for a P2 type sodium ion battery according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: (1) The sodium source, nickel source, manganese source, gadolinium source and barium source are mixed evenly according to the stoichiometric ratio and then subjected to the first heat treatment to obtain the P2 matrix Na a Ni x Mn 2x G y Ba z O2; the first heat treatment holding temperature is 850 ℃ ~ 1050 ℃, the holding time is 8 to 16 hours, the heating rate is 3 to 5 ℃ / min, and the sintering atmosphere is air; (2) The Na obtained in step (1) a Ni x Mn 2x G y Ba z O2 material is crushed to a particle size of D00 ≥ 0.5 μm, 4.0 μm ≤ D50 ≤ 5.5 μm, and D100 ≤ 14 μm; (3) the material obtained in step (2) is uniformly mixed with Ti(HPO4)2 and MgHPO4 according to a mass ratio, and then subjected to a second heat treatment to obtain a high-voltage and high-rate P2 type sodium ion battery positive electrode material; the second heat treatment has a holding temperature of 650° C. to 850° C., a holding time of 4 to 10 hours, a heating rate of 3 to 5° C. / min, and an air sintering atmosphere; (4) The material obtained in step (3) is crushed to a particle size satisfying D00 ≥ 0.6 μm, 4.5 μm ≤ D50 ≤ 6.5 μm, and D100 ≤ 16 μm.

8. The method for preparing a positive electrode material for a P2 type sodium ion battery according to claim 7, characterized in that: The sodium source is one or more of sodium carbonate, sodium hydroxide and sodium oxalate; the nickel source is one or more of its oxides, oxalates or hydroxides; the manganese source and gadolinium source are their corresponding oxides; and the barium source is one or both of its carbonates and oxalates.

9. A sodium ion secondary battery, characterized in that: The sodium ion secondary battery comprises the P2 type sodium ion battery positive electrode material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Composite active material for lithium-ion battery and preparation method of composite active material, lithium-ion battery electrode paste, positive electrode or negative electrode and lithium-ion battery

    CN106505205A

  • Composite positive electrode material, preparation method thereof and lithium ion battery

    CN114614006A

  • Coated modified material and application thereof in preparation of sodium ion battery positive electrode material

    CN116646513A

  • Nonaqueous electrolyte secondary battery

    US20200266420A1

  • Positive electrode material, preparation method therefor, and lithium ion secondary battery

    US20230077131A1